Meaning of Local Language Expression of Pasang Ri Kajang and Its Implication for Language Teaching - Marliana, Anis; Anshari, -; Amir, Johar (International Journal of Language Education, 2021)
Pasang Ri Kajang is an Ammatoa community life guidance which is consist of a collection of ancestral mandates. The formulation of the problem in this study is how Pasang Ri Kajang, which is Local Wisdom, contains aspects of Proverbs, Proverbs and Literature Characteristics the purpose of this research study is:Getting a picture of how Pasang Ri Kajang that is a Local Wisdom contains aspects of Proverbs, Characteristics and Literature. Data collection techniques through informants through observation, interviews, recordings and documentation. Sources of data in this study were obtained from primary datasources, namely customary stakeholders and community leaders. Data were collected from July 2019 to September 2019. Research findings and conclusions that the contents of Pasang Ri Kajang include proverbs. Types of proverbs: proverb, thimble or slogan. Pasang Ri Kajang, if observed almost all elementsof literary works contained in Pasang ri Kajang. Literary elements, namely: thoughts, experiences, ideas, feelings, enthusiasm, beliefs, beliefs, expressions, expressions, forms, and language criteria for proverbs that are the structure that must not change, the beauty of the language lies in the repetition of words at the beginning of the sentence with use the word, reflecting events that occur in a society, proverbs are formed and created with a reliable and beautiful language bond so that the proverb will be attached to the mouth of the community and hereditary Celoka and Talibun.